Epidemiology and Survival of Marginal Zone Lymphoma in Colombian Patients: An Observational Retrospective Study - Juan F. Combariza-Vallejo; Rocío Orduz-Rodriguez; Natalia Gomez-Lopera; Claudia C. Colmenares-Mejia; Monica S. Benavides-Rojas; Yesica M. Calderon-Ortega; Marcela Godoy-Corredor; Mario Arturo Isaza-Ruget (JCO Global Oncology)
PURPOSEMarginal zone lymphomas (MZLs) are indolent non-Hodgkin lymphomas, categorized into three subtypes: extranodal, splenic, and nodal MZL (NMZL). MZL epidemiology and outcomes in Latin America remain underexplored.MATERIALS AND METHODSThis retrospective cohort study included patients with MZL in Colombia from 2000 to 2023. Patients were followed for at least 24 months from diagnosis. The primary outcomes were real-world overall survival (Rw-OS) and real-world progression-free survival (Rw-PFS).RESULTSThe cohort included 103 patients (63.1% female, 36.9% male) with a median age of 61.8 years. MALT lymphoma was the most common subtype (61.1%), followed by splenic MZL (26.2%) and NMZL (12.7%). The 60-month Rw-OS was 86.4%, and the Rw-PFS was 77.2%.CONCLUSIONMZL in Colombian patients exhibits varied clinical presentations and survival outcomes. This study underscores the importance of early detection and subtype-specific management of MZL.